Evaluating and validating ESP testing in a specific context: stakeholders’ perspectives / Fahima Mohamed Bannur - Mohamed Bannur, Fahima (Institute of Graduate Studies, UiTM, 2016)
The purpose of this study is to evaluate the validity of an existing English test in order to examine its potential and shortcomings in assessing the engineering students’ English ability. The test was built mainly to measure grammar and reading ability, while adopting recognition testing techniques. The focus on the validity event for the ESP reading test arose from the urgent need of the University of Tripoli, Libya as well as students’ appeal for an improved English test, where thousands of students from different engineering departments at the faculty of engineering study English (ESL) as a compulsory course and take the ESP test to carry on their academic study at the faculty. The current method of providing the English test to these students presents the university with some problems in terms of test design, construction, content, efficiency, reliability and validity. These are significant aspects for any validation process, and to date, they have not been addressed formally at the university. To achieve this, a framework for validating a reading test (Weir 2005) was adopted throughout the study. The framework is instructive and comprehensive in nature. It has five components and various parameters that ensure meaningful and typical test validity process in all test stages which include a ‘priori’, during and a ‘posteriori’ of the test event…